Tinjauan Hukum Islam terhadap Poin yang Diberikan kepada Mitra Payment Point Online Banking (PPOB) dalam Platform Bukakios - Agustine, Hendra Karunia; Mahardika, Muhamad Azaria (AL-MASHALIH (Journal of Islamic Law), 2025)
Bukakios is a digital transaction service application or it is commonly recognized as PPOB (Payment Point Online Banking). In this application, the partners are able to earn points after initiating a transaction. With respect to its mechanism, the points earned by a Bukakios partner are still considered uncertain because it is still unclear regarding the status of the points. In other words, it is also probable that the aforementioned points contain elements of gharar or usury. The present study aims to investigate the mechanism for earning points in the Bukakios application. In addition, this study also aims to scrutinize the points earned by Bukakios partners from their transactions and how Islamic law perspective scrutinizes the points awarded to online banking payment point partners on this application. This study employs qualitative research by using field research design. The data were obtained through observation, interview, and documentation. According to the analysis of the sale and purchase agreement as well as wakalah bil ujrah (regarding the pillars and conditions), the findings indicate that the points awarded to PPOB partners on Bukakios application is considered as a mere sale and purchase agreement. It is because it already fulfills the pillars and conditions of selling and buying, hence, it is permissible in Islamic law point of view. These points, however, are categorized as an ujrah given by this application to its partners because they have sold Bukakios application products to consumers and they are legally acceptable in Islam since they have fulfilled the pillars and requirements of wakalah bil ujrah.